Integrated use of georadar, electrical resistivity, and SPT for site characterization and water content estimative - Farias, Érdeson Soares; Machado, Sandro Lemos; Giacheti, Heraldo Luiz [UNESP]; Cerqueira, Alexsandro Guerra (ABMS - Brazilian Association for Soil Mechanics and Geotechnical Engineering, 2023)
Geophysical methods are potent tools for geotechnical site characterization in a non-destructive way. They improve the extrapolation of punctual data from direct survey methods, allowing a fast and cost-effective evaluation of large areas. Ground Penetrating Radar (GPR) and DC electrical resistivity (ER) are the most requested methods for geotechnical and geoenvironmental applications. Their use, however, is usually uncoupled, with no sharing of information from one method to another to improve data interpretation. This case study illustrates the development of protocols and scripts in R© programming language for ER and GPR data analysis with Standard Penetration Tests (SPT) data to produce more accurate information on subsurface conditions concerning lithology, water content, and groundwater table (GWT) position. The SPT data were used to associate resistivity ranges with different soil lithologies and GPR pulse velocities for estimating the soil water content. Estimated water content values aided in interpreting ER data and locating the groundwater table. The contacts between layers in the radargrams allowed the refinement of the ER model, rendering 3D volumes for each soil layer in situ.
Keywords: Coupled surveys; ERT; GPR; In situ tests; Site characterization; SPT